Special Exercises For Developing Hurdle Stride In Different Phases Of Youth 400m Hurdles - Mohameed, Ahmed; Kazem, Hasnaa (Journal of Physical Education, 2016)
The problem of the research lies in the special endurance weakness in many youth hurdlers that leads to great decline in achievement, the researchers hypothesized statistical difference in pre and posttests in special endurance. The researcher used the experimental method. The subjects were (6) youth hurdles. The researcher selected many tests; 150m hurdles test, 200m hurdles test, and 300m hurdles test to measure special speed endurance. Pretests were conducted followed by the training program. The training program consisted (8) weeks with (3) training sessions per week. After posttests, the data was collected and treated using proper statistical methods. The results showed that special speed endurance training lead to the development of some special physical abilities as well as hurdle stride in the third, fifth, and eighth hurdles. The training program developed the stride performance level in youth hurdlers in 150m, 200m, and 300m hurdles.